First records of Pieza Evenhuis, 2002 (Diptera: Mythicomyiidae: Mythicomyiinae) from Colombia, with description of a new species from arid zones of a Tropical dry forest - Ramos-Pastrana, Yardany; Córdoba-Suarez, Eric; Evenhuis, Neal. L (Zootaxa, 2023)
Pieza Evenhuis, 2002 has a New World distribution and is a poorly studied group in the Neotropical Region, and completely unknown in Colombia. We recorded for the first time the genus Pieza in Colombia with two species, namely Pieza rafaeli Mendes et al., 2019 and we described Pieza globosa sp. nov. (type-locality: Sabanalarga, Boca de Niquia) from arid zones of a Tropical dry forest. Illustrations and a distribution map are presented.